Islamic Religious Teachers Shape Moral Formation in Elementary Learners: Guru Pendidikan Agama Islam Membentuk Akhlak Peserta Didik Sekolah Dasar - Rosfiah Urbani; Saprin Saprin; Muhammad Rusmin B. (Academia Open, 2026)
General Background: Islamic education in Indonesia is positioned as a fundamental aspect of national schooling, emphasizing moral formation aligned with the goals of the 2003 National Education System Law and Islamic values in daily life. Specific Background: SDIT Mukhlisiin Gowa applies an integrated Islamic learning system where Islamic Religious Education and Character teachers are assigned to cultivate students’ behavior through habituation, guidance, and supervision. Knowledge Gap: However, field observations show inconsistencies between the school’s Islamic vision and students’ actual behavior, including limited discipline in worship routines, weak responsibility, and emerging negative attitudes influenced by external environments. Aims: This study investigates the role of Islamic Religious Education and Character teachers in shaping the moral conduct of fifth-grade students and identifies supporting and inhibiting factors. Results: The findings reveal that teachers serve as moral exemplars, mentors, motivators, and supervisors through practices such as daily worship habituation, persuasive guidance, religious reinforcement, communication with parents, and creative pedagogical strategies. Internal support includes teacher role-modeling and an Islamic school environment, while external challenges arise from digital exposure, peer environments, and inconsistent family support. Novelty: This study highlights the integrative function of teacher-led moral cultivation as both instructional and cultural practice in an Islamic elementary context, where spiritual, behavioral, and social guidance operate simultaneously. Implications: The outcomes encourage strengthening religious program policies at school level, enhancing instructional creativity for teachers, reinforcing parental collaboration, and motivating students to participate actively in moral formation, contributing to sustainable Islamic character development in basic education. Highlights: • Teachers function simultaneously as exemplars, mentors, and motivators in daily school practice• School religious culture and parent collaboration support consistent student moral habituation• External environment and digital access remain primary barriers requiring collaborative intervention Keywords Islamic Education; Moral Formation; Teacher Roles; Character Development; Elementary Learners